Discipline as a Subject of Pedagogy (Eurasian Research Bulletin, 2022)
In the article, discipline is considered as a condition of the socio-legal and ethicalcultural factor, which are designed to ensure socio-economic stability, prevent threats, and ensure the country's security. In the scientific literature on this issue, there are various points of view, sometimes contradicting each other. The purpose of this article is a comprehensive analysis of the phenomenon of discipline, paying special attention to the socio-psychological features of this phenomenon, the scientific and philosophical interpretation of the category of discipline. The concept of "discipline" is an object of an interdisciplinary nature, where each area approaches the issue taking into account the specifics of this area of knowledge. The authors came to the conclusion that the discipline of all subjects of international, regional and interpersonal relations is a condition for regulating the problems of social progress.